Non-therapeutic play to overcome negative emotional symptoms and improve emotional intelligence in children aged 3–7: a systematic review - Veraksa, Alexander N.; Plotnikova, Valeriya A.; Sukhikh, Vera L.; Kornienko, Dmitry S.; Rudnova, Natalia A. (Frontiers in Psychology, 2025)
Play therapy is an effective approach to reduce emotional symptoms, stress and develop emotional sphere in early childhood. But the organization of therapy requires long-term specialized training and a significant number of sessions, making it inaccessible in public institutions. This systematic review aims to analyze the potential and mechanisms of play outside of the therapeutic setting for overcoming emotional symptoms, develop emotional regulation and resilience in preschool-aged children. Using the PRISMA method, we selected 33 articles for qualitative analysis from the 9,639 published articles over the past 5 years found through PubMed, ScienceDirect, and Scopus. The effectiveness of pretend play, play with rules, digital play, and outdoor play for addressing emotional symptoms and improving mental health was revealed. It was shown that play outside of the therapeutic setting is widely used to improve emotional intelligence and its components, decrease anxiety, aggression, and fear. In accordance with the cultural-historical approach, seven generalized blocks of play mechanisms were identified to enhance children’s mental well-being and promote development. Pretend play was found to have the greatest corrective and developmental potential, due to the diverse mechanisms involved. The findings of this review may be used to plan future research and improve educational practice in public kindergartens.